Climate, peace, security and migration in Mozambique - Maviza, Gracsious; Synnestvedt, Thea; Caroli, Giulia; Tarusarira, Joram; Sax, Niklas (2023)
Climate-related extreme weather events and conflict are making their mark globally, co-occurring and reinforcing each other in a vicious circle, complicating efforts to build and sustain peace. In Southern Africa, Mozambique is a prime example of how the adverse effects of climate change interact with conflict, fragility and displacement in multifaceted ways, eroding social capital and social cohesion and even making conflict dynamics more pronounced and intractable. As the impacts of climate change become clearer, the consequences for peace and security have become a key concern for policymakers and practitioners. The adverse impacts of climate variability, extremes and environmental degradation exacerbate the causes and effects of conflict and undermine efforts to build and sustain peace. While these dynamics are highly context-specific, they tend to emerge in fragile and conflict-affected settings (FCASs) where communities struggle to sustain resilient food, land, and water systems (FLWSs). Livelihood challenges and rising food, fertiliser, and input prices are further compounded by climate change and unsustainable resource use, poor governance, and weak social cohesion.